2019
DOI: 10.1038/s41467-019-13618-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-genetic profiling reveals limited cross-resistance between antimicrobial peptides with different modes of action

Abstract: Antimicrobial peptides (AMPs) are key effectors of the innate immune system and promising therapeutic agents. Yet, knowledge on how to design AMPs with minimal cross-resistance to human host-defense peptides remains limited. Here, we systematically assess the resistance determinants of Escherichia coli against 15 different AMPs using chemical-genetics and compare to the cross-resistance spectra of laboratory-evolved AMP-resistant strains. Although generalizations about AMP resistance are common in the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 70 publications
2
41
0
Order By: Relevance
“…have shown that ARB frequently present collateral sensitivity to antimicrobial peptides (Lázár et al, 2018) and that, importantly, some antimicrobial peptides present limited resistance or crossresistance (Kintses et al, 2019;Spohn et al, 2019). From a conservative point of view, based on the use of the drugs we already have, it would be desirable to fight AR using evolution-based strategies for developing new drugs or treatment strategies.…”
Section: Controlling Resistance: Local and Global Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that ARB frequently present collateral sensitivity to antimicrobial peptides (Lázár et al, 2018) and that, importantly, some antimicrobial peptides present limited resistance or crossresistance (Kintses et al, 2019;Spohn et al, 2019). From a conservative point of view, based on the use of the drugs we already have, it would be desirable to fight AR using evolution-based strategies for developing new drugs or treatment strategies.…”
Section: Controlling Resistance: Local and Global Interventionsmentioning
confidence: 99%
“…Furthermore, antimicrobial peptides, with a dual role as immunomodulators and antimicrobials, may also help fight infections ( Hancock et al, 2016 ). In fact, some works have shown that ARB frequently present collateral sensitivity to antimicrobial peptides ( Lázár et al, 2018 ) and that, importantly, some antimicrobial peptides present limited resistance or cross-resistance ( Kintses et al, 2019 ; Spohn et al, 2019 ).…”
Section: Controlling Resistance: Local and Global Interventionsmentioning
confidence: 99%
“…4a). Increase in PLL-FITC binding has previously also been correlated with increased susceptibility to the action of antimicrobial peptides (5, 32, 33). In contrast, zeta potential values did not show a strong correlation with Ped-488 (r 2 = 0.06, r s = −0.62, Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Spohn et al (196) have highlighted the influence of physicochemical characteristics of HDPs, including the proportion of polar AAs, cationicity, and hydrophobicity, on the risk of developing HDP-related AMR, thereby providing invaluable insights into the design of future HDPs. Reassuringly, cross resistance between HDPs was found to be limited to those with similar modes of action, underscoring the importance and necessity of having HDPs with different antimicrobial mechanisms within the therapeutic armamentarium of antimicrobials (197). With the advancement in peptide design strategy, synthesis techniques and AI technology, it is hopeful that clinical deployment of HDP-based treatment for a range of diseases will soon become a reality.…”
Section: Risk Of Amr Related To Hdpmentioning
confidence: 99%